2018
DOI: 10.1038/mi.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Unique invariant natural killer T cells promote intestinal polyps by suppressing TH1 immunity and promoting regulatory T cells

Abstract: CD1d-restricted invariant natural killer T (iNKT) cells are known as potent early regulatory cells of immune responses. Besides the established roles in the regulation of inflammation and autoimmune disease, studies have shown that iNKT cells have important roles in tumor surveillance and the control of tumor metastasis. Here we found that absence of iNKT cells dramatically decreased the total number of intestinal polyps in APCMin/+ mice, a model for colorectal cancer. Polyp iNKT cells were enriched for IL-10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 46 publications
8
71
0
Order By: Relevance
“…Consistent with this, NKT cells are the major producers of IL‐4 in this tissue, and after stimulation of mLN lymphocytes with PMA/ionomycin, iNKT cells constitute up to 60% of the IL‐4‐producing cells . Finally, NKT10 cells are also found in the intestine of transgenic mouse models of colorectal cancer (APC Min/+ mice) . It is worth noting that while the majority of iNKT cells found in the adult murine gut in steady state are T‐bet + NKT1s, it is possible that other iNKT cell subsets (or precursors) could be recruited/expanded under certain inflammatory conditions ultimately shaping the functional capabilities of the local iNKT cell population.…”
Section: Nkt Cells In the Intestinal Compartmentmentioning
confidence: 89%
See 2 more Smart Citations
“…Consistent with this, NKT cells are the major producers of IL‐4 in this tissue, and after stimulation of mLN lymphocytes with PMA/ionomycin, iNKT cells constitute up to 60% of the IL‐4‐producing cells . Finally, NKT10 cells are also found in the intestine of transgenic mouse models of colorectal cancer (APC Min/+ mice) . It is worth noting that while the majority of iNKT cells found in the adult murine gut in steady state are T‐bet + NKT1s, it is possible that other iNKT cell subsets (or precursors) could be recruited/expanded under certain inflammatory conditions ultimately shaping the functional capabilities of the local iNKT cell population.…”
Section: Nkt Cells In the Intestinal Compartmentmentioning
confidence: 89%
“…In C57Bl/6 mice, NKT1 cells are highly abundant and especially enriched in liver, spleen and thymus, NKT2 cells are abundant in mesenteric lymph node (mLN), and NKT17 cells are enriched in lungs as well as in inguinal (iLN), axillary (aLN) and cervical (cLN) LNs . NKT10 cells preferentially accumulate in adipose tissue in homeostasis, but can be induced in response to immunisation and are found in the intestine of transgenic mouse models of colorectal cancer (APC Min/+ mice) . On the other hand, NKT FH and NKTregs have been only detected in mice during immune responses .…”
Section: Nkt Cells: An Overviewmentioning
confidence: 98%
See 1 more Smart Citation
“…158 The tumour immunology of the colorectal adenoma has been largely ignored, perhaps because of the relative difficulty in collecting sufficient, fresh human colorectal adenoma tissue and absence of a suitable animal model. 159 However, regulation of host immune surveillance as a mechanism of primary CRC chemoprevention activity remains a valid hypothesis for both seAFOod trial interventions. 160 We have recently reported that mixed ω-3 PUFA treatment is associated with an increase in abundance of SCFA-producing bacteria in the colon.…”
Section: Recommendations For Researchmentioning
confidence: 99%
“…For example, control of homeostasis in the visceral adipose tissue is dependent on IL-10 from NKT cells 14 , as are some aspects of cardiac remodeling 15 . Autoimmune diseases ranging from alopecia areata 16 to insulin-dependent diabetes mellitus 17 are associated with IL-10 producing NKT cells 18,19 , as is the growth of intestinal polyps that can lead to cancer 20 .…”
mentioning
confidence: 99%